2010
DOI: 10.1159/000323175
|View full text |Cite
|
Sign up to set email alerts
|

Is Capecitabine Efficacious in Triple Negative Metastatic Breast Cancer?

Abstract: Background: Recent data suggest that capecitabine may have little efficacy in women with metastatic triple negative breast cancer (TNT). We have therefore retrospectively analysed capecitabine outcome in the TN subgroup of patients with locally advanced or metastatic breast cancer treated in our unit. Patients and Methods: All TNT patients on our prospectively maintained database with locally advanced or metastatic breast cancer who were given capecitabine as 1st-, 2nd- or 3rd-line chemotherapy were assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The apatinib and capecitabine group exhibited a higher PFS than the capecitabine group ( P = .001). A retrospective study with 363 TNBC patients showed that capecitabine monotherapy achieved a ORR of 21% and a DCR of 33% [ 25 ] ; our study had a similar efficacy with it and the ORR in capecitabine group was 13.4%, and the DCR in capecitabine group was 31.8%. Although in apatinib and capecitabine group, it was 40.9% and 68.2%.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The apatinib and capecitabine group exhibited a higher PFS than the capecitabine group ( P = .001). A retrospective study with 363 TNBC patients showed that capecitabine monotherapy achieved a ORR of 21% and a DCR of 33% [ 25 ] ; our study had a similar efficacy with it and the ORR in capecitabine group was 13.4%, and the DCR in capecitabine group was 31.8%. Although in apatinib and capecitabine group, it was 40.9% and 68.2%.…”
Section: Discussionsupporting
confidence: 68%
“…[ 22 24 ] A retrospective study including 363 patients with TNBC treated with capecitabine demonstrated that capecitabine is a treatment option for patients with TNBC in advanced disease including first-line and second/third-line. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“… 8 Capecitabine is a prodrug of 5-FU. 13 , 14 The DX regimen has been widely used as the first-line treatment for advanced breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Kotsori et al [23] retrospectively analyzed 89 TNBC patients who received capecitabine monotherapy as first- to third-line therapy in Royal Marsden hospital. The ORR and CBR were 21 and 33%, respectively.…”
Section: Discussionmentioning
confidence: 99%